Cerebrovascular autoregulation monitoring and patient‐centred outcomes after cardiac surgery: a systematic review. Issue 5 (24th March 2018) - Chan, B.; Butler, E.; Frost, S. A.; Chuan, A.; Aneman, A.
Abstract : Background: Impaired cerebrovascular autoregulation (CVAR) is observed in up to 20% of cardiac surgical patients. This systematic review aims to evaluate the association between impaired CVAR, measured by current monitoring techniques, and patient‐centred outcomes in adults following cardiac surgery. Methods: MEDLINE, EMBASE, PubMed, MEDLINE In‐Process and Cochrane Library were systematically searched through 8 December 2017. Studies were included if they assessed associations between CVAR and patient‐centred outcomes in the adult cardiac surgical population. The primary outcome of this systematic review was mortality. Secondary outcomes were stroke, delirium and acute kidney injury. Risk of bias was systematically assessed, and the GRADE methodology was used to evaluate the quality of evidence across outcomes. Results: Eleven observational studies and no randomised controlled trials met the inclusion criteria. Due to methodological heterogeneity, meta‐analysis was not possible. There was a high risk of bias within individual studies and low quality of evidence across outcomes. Of the included studies, one assessed mortality, five assessed stroke, four assessed delirium, and three assessed acute kidney injury. No reliable conclusions can be drawn from the one study assessing mortality. Interpretation of studies investigating CVAR and stroke, delirium and acute kidney injury was complicated by the lack of standardisation of monitoring techniques as well as varying definitions of impaired CVAR. Conclusions: There is a paucity of high quality evidence for CVAR monitoring and its associations with outcome measures in post‐cardiac surgical patients, highlighting the need for future studies.